From Asymmetric Coexistence to Inclusive-Relational PAI: Constructing the Meaning of Tolerance in Multicultural Schools - Salsabila Yuspia Ali; Muhamad Ihsan Hasanudin; Muhammad Iqbal Fathurahman (UIN Sunan Gunung Djati Bandung, 2025)
This study examines how Muslim and non-Muslim students construct the meaning of tolerance within the learning ecosystem of Islamic Religious Education (Pendidikan Agama Islam, PAI) in a multicultural school. Employing a qualitative narrative-thematic design, the study was conducted at SMAN 1 Banjaran, Bandung Regency. Data were collected through in-depth interviews, observation, and documentation involving Muslim students, non-Muslim students, PAI teachers, and guidance and counseling teachers. The findings indicate that tolerance cannot be understood merely as the absence of conflict. Rather, it is a relational experience shaped by language, religious humor, symbols, group work, and majority-minority relations. Interreligious relations among students tend to reflect asymmetric coexistence: students are able to befriend and cooperate with one another, yet their experiences of safety and recognition are not fully equal. This study proposes the concept of Inclusive-Relational PAI, an approach to PAI learning that remains rooted in Islamic teachings while being attentive to language, safe spaces, dialogue, and the experiences of students from different religious backgrounds. The findings highlight the important role of PAI teachers as curators of religious language and facilitators of fair interreligious interaction grounded in inclusive civility. Keywords: Islamic Religious Education; tolerance; multicultural school; asymmetric coexistence; Inclusive-Relational PAI.